Aberrant sialylation in a patient with a HNF1α variant and liver adenomatosis - Luisa Sturiale; Marie-Cécile Nassogne; Angelo Palmigiano; Angela Messina; Immacolata Speciale; Rosangela Artuso; Gaetano Bertino; Nicole Revencu; Xavier Stephénne; Cristina De Castro; Gert Matthijs; Rita Barone; et al. (iScience, 2021)
Summary: Glycosylation is a fundamental post-translational modification of proteins that boosts their structural diversity providing subtle and specialized biological properties and functions. All those genetic diseases due to a defective glycan biosynthesis and attachment to the nascent glycoproteins fall within the wide area of congenital disorders of glycosylation (CDG), mostly causing multisystem involvement. In the present paper, we detailed the unique serum N-glycosylation of a CDG-candidate patient with an unexplained neurological phenotype and liver adenomatosis harboring a recurrent pathogenic HNF1α variant. Serum transferrin isoelectric focusing showed a surprising N-glycosylation pattern consisting on hyposialylation, as well as remarkable hypersialylation. Mass spectrometry-based glycomic analyses of individual serum glycoproteins enabled to unveil hypersialylated complex N-glycans comprising up to two sialic acids per antenna. Further advanced MS analysis showed the additional sialic acid is bonded through an α2-6 linkage to the peripheral N-acetylglucosamine residue.